The McAvoy sisters book of secrets : a novel - Fader, Molly (Graydon House, 2020)
It's been seventeen years since the tragic summer the McAvoy sisters fell apart. Lindy, the wild one, left home, carved out a new life in the city and never looked back. Delia, the sister who stayed, became a mother herself, raising her daughters and running the family shop in their small Ohio hometown on the shores of Lake Erie. But now, with their mother's ailing health and a rebellious teenager to rein in, Delia has no choice but to welcome Lindy home. As the two sisters try to put their family back in order, they finally have the chance to reclaim what's been lost over the years: for Delia, professional dreams and a happy marriage, and for Lindy, a sense of home and an old flame--and best of all, each other. But when one turbulent night leads to a shocking revelation, the women must face the past they've avoided for a decade. And there's nothing like an old secret to bring the McAvoy women back together and stronger than ever.